ECONOMIC VALUE ADDED (EVA) SEBAGAI ALTERNATIF UNTUK MENILAI KINERJA KEUANGAN PADA PT SEMEN TONASA - Putri Nurwana; Mukhammad Idrus; Azwar Anwar (STKIP Subang, 2026)
This study aims to determine the financial performance obtained by analyzing data using the Economic Value Added (EVA) method at PT Semen Tonasa for the 2022-2024 period. The research variable is Economic Value Added (EVA), which is a single variable. The population in this study is the financial statements of PT Semen Tonasa for the 2022-2024 period, while the sample in this study is the balance sheet and income statement of PT Semen Tonasa for the 2022-2024 period. The data is based on the financial statements of PT Semen Tonasa on the company's official website https://www.sementonasa.co.id/. Data analysis was carried out using the Economic Value Added (EVA) method. The results of the analysis using the Economic Value Added (EVA) method indicate that the overall financial performance of PT Semen Tonasa is good. Where the company has succeeded in creating economic added value by generating a positive EVA value (EVA > 0). Keywords: Economic Value Added, Financial Performance